Fostering experiential learning of neurocognitive skills in brain injury tele-rehabilitation: bridging gaps in remote training by integrating scenario-based digital experiences with coaching - Loya, Fred; Binder, Deborah; Rodriguez, Nicholas; Buchanan, Bruce; Novakovic-Agopian, Tatjana; Chen, Anthony J.-W. (Frontiers in Human Neuroscience, 2025)
Dysregulation of brain state is common following traumatic brain injury (TBI), contributing to long-term difficulties in important life pursuits, spanning school, work, and beyond. Brain state dysregulation makes it difficult to effectively organize and direct cognition and behavior to accomplish any number of goals, resulting instead in difficult-to-understand combinations of neurocognitive and emotional symptoms: distractibility, forgetfulness, poor follow-through, irritability, reduced frustration tolerance, and becoming easily overwhelmed. Given underlying heterogeneity with neurocognitive-emotional symptoms, it may be highly efficient to train use of state regulation skills (SRS) as a generalizable approach to facilitate processing of neurocognitive demands encountered along individual goal pathways. In this report, we present an innovative system of guided experiential skill learning of goal-directed SRS – one that rationally integrates experiential digital technology designed to practice applying and integrating SRS directly into goal-based functional challenges with therapist-led training to maximize skill learning, transfer, and generalization. Moreover, we designed this system specifically to bridge important gaps that interfere with skill learning when individuals are remote from therapists. To advance the integration of technology into rehabilitation neuroscience, we present this communication as a hybrid of intervention design (introducing principles and features), “user experiences” (sharing vignettes informative of the value of technology integration into the learning process), and a controlled, proof-of-principle pilot intervention study for a small cohort of individuals (n = 18) with chronic TBI (assessing the plausibility of strengthening goal-directed functioning, as indexed by performance on neurocognitive assessment tasks and complex functional tasks, as well as ratings of personal life functioning). Data suggest that a technology-augmented remote guided experiential learning approach may bridge important gaps in skill learning to help individuals improve goal-directed functioning. This line of work will inform further advances in remote neuro-cognitive rehabilitation.